CARDIOVASCULAR RESPONSES TO COLD WATER EXPOSURE: PHYSIOLOGICAL MECHANISMS, POTENTIAL BENEFITS, AND CLINICAL RISKS: A LITERATURE REVIEW - Patryk Matuszczak; Agata Pszczółka; Joanna Kozak; Gabriela Bajor; Kacper Melka; Mikołaj Szulewski; Aleksandra Salagierska; Patrycja Machno; Wiktoria Jurczyk-Florkiewicz; Zofia Gniadek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Cold water exposure (CWE), including cold water immersion, winter swimming, and cryotherapy, is increasingly used to support recovery and wellbeing. However, its cardiovascular effects remain controversial, involving both potential adaptive mechanisms and clinically relevant risks.Objective: This review aimed to synthesize current evidence on cardiovascular responses to acute and repeated cold water exposure.Methods: A structured search of publications from 2020–2025 was conducted using PubMed. Following screening, 20 studies were included, comprising experimental investigations, reviews, and case reports. Evidence was qualitatively analyzed with emphasis on cardiovascular outcomes and safety.Results: Acute exposure triggers the cold shock response characterized by sympathetic activation, increases in heart rate and blood pressure, and complex autonomic modulation. Transient arrhythmias were reported in some individuals. Repeated exposure was associated with favorable changes in selected metabolic markers and improved perceived wellbeing, although findings were heterogeneous.Conclusions: CWE induces significant cardiovascular responses with both adaptive and potentially harmful effects. Individual risk assessment and further longitudinal studies are necessary.